RESILIENSI WARGA BINAAN PEMASYARAKATAN PEREMPUAN : KAJIAN LITERATUR - Sayekti Dwi Cahyani; Megah Andriany (NURSE: Journal of Nursing and Health Science, 2022)
The incidence of mental health problems in women prisoners is higher than men. A mental health problem often experienced by women prisoners isdepression. Women prisoners need resilience to adapt and deal with threats that arise in the prison environment, so they do not experience psychological problems. Recently, limited review regarding studies about resilience of women prisoners showing different results. The purpose was to describe resilience and the influencing factors in women prisoners. The method is literature review by searching articles through the Science direct, Google Scholar, EBSCO, PubMed and SCOPUS. The results found 12 articles. The resilience of women prisoners is high because of thesuccess of coaching by correctional institution, so that it will have emotional intelligence, able to show an attitude of adaptation to life changes in correctional. Women prisoners with low resilience cannot adapt to changes in the environment and face difficulties in prison and will tend to have symptoms of PTSD, anxiety, and depression. The women prisoners’ resilience is influenced by internal factors (hardiness, psychological adjustment, coping flexibility, and self-esteem) and external factors such as social support. In conclusion, resilience of women prisoners is highdemonstrated by staying calm in dealing with new conditions, having a way of solving problems, establishing social relationships and optimism. Nurses and correctional institutions can maintain the resilience by developing interventions and coaching programs.